MICRO, SMALL AND MEDIUM ENTERPRISES IN TOURIST DESTINATIONS IN SITU GINTUNG, SOUTH TANGERANG, BANTEN PROVINCE - Reno Catelya Dira Oktavia; Oktovianus; Alda Chairani (International Journal Management and Economic, 2025)
This research aims to understand the challenges MSMEs face around the Situ Gintung tourism destination, South Tangerang, Banten Province, and provide appropriate policy recommendations. The research method used is a qualitative approach focusing on case studies. Surveys, interviews, and document analyses were used to gain an in-depth understanding of MSME challenges and formulate policy recommendations. The research results show that access to business capital, efficient business management, and competition with other MSMEs are the main problems. Policy recommendations include providing training, easy access to business capital, promotion of MSME products, and improving infrastructure. In conclusion, this update is expected to increase the competitiveness and contribution of MSMEs in local economic development and maintain the ecosystem and culture in the Situ Gintung tourist destination